Hedging the hard way: Russia's response to world disorder. Issue 2 (14th March 2016) - Holslag, Jonathan
Abstract : This paper posits that Russia's role during the Ukrainian Crisis presaged a strategy of hard hedging. Confronted with the apparent threat of growing influence of the West and growing influence of China, Russia has responded with a policy of hard hedging that is characterized by an emphasis on military power, sovereignty and autonomy. The paper comes to that conclusion by reconstructing shifts and continuity in Russia's behaviour between 2014 and 2015, considering a wide range of economic, political, and military indicators.